Cultural histories of India: subaltern spaces, peripheral genres, and alternate historiography - Banerjee, Rita (Routledge studies in South Asian history, 2020)
Introduction -- Part 1: Investigating Cultural Practices, Fashioning Identities, and Travel Literature -- 1 John Locke's India: Religion, Revelation, and Enthusiasm, Daniel Carey -- 2 Encountering the 'Sati': Early Modern English Travel Narratives and the Politics of Exoticization, Rita Banerjee -- 3 Indian Travel Writing in the Age of Empire: Mobility and Cosmopolitan Nationalism, Pramod K. Nayar -- Part 2: Alternate Histories, Divergent Concepts, and Subaltern Spaces of Resistance -- 4 Patriots in Kala Pani? Writing Subaltern Resistance into the Nationalist Memory, Philipp Zehmisch -- 5 Reading Bhikshu Bodhanand's Mool Bharatvasi aur Arya: Reflections on an Alternative History of the 'Beginnings' of Indian Civilization, Tapan K. Basu -- 6 Enacting Resistance in History and Fiction: Counter-narratives of Tribal Historiography in Mahasweta Devi's Writings, Debarati Das and Rita Banerjee -- 7 We must create a history of India in living terms: Patrick Geddes and Aspects of Sister Nivedita's Writings on Indian History, Arpita Mitra -- Part 3: Writing History and Engaging with Peripheral Genres -- 8 Cassetted Emotions: Intimate Songs and Marital Conflicts in the Age of Pravasi (1970-1990), P. K. Yasser Arafath -- 9 Framing History, Precarity, and Trauma: A Study of Nandita Das's Firaaq, Nishat Haider.